Boarding Injuries: The Long and the Short of It. (10th February 2014) - Fabian, Leslie A.; Thygerson, Steven M.; Merrill, Ray M.
Abstract : As the popularity of longboarding increases, trauma centers are treating an increased number of high severity injuries. Current literature lacks descriptions of the types of injuries experienced by longboarders, a distinct subset of the skateboarding culture. A retrospective review of longboarding and skateboarding injury cases was conducted at a level II trauma center from January 1, 2006, through December 31, 2011. Specific injuries in addition to high injury severity factors (hospital and intensive care unit (ICU) length of stay (LOS), Injury Severity Score (ISS), patient treatment options, disposition, and outcome) were calculated to compare longboarder to skateboarder injuries. A total of 824 patients met the inclusion criteria. Skull fractures, traumatic brain injuries (TBI), and intracranial hemorrhage (ICH) were significantly more common among longboard patients than skateboarders (P < 0.0001 ). All patients with an ISS above 15 were longboarders. Hospital and ICU LOS in days was also significantly greater for longboarders compared with skateboarders (P < 0.0001 ). Of the three patients that died, each was a longboarder and each experienced a head injury. Longboard injuries account for a higher incidence rate of severe head injuries compared to skateboard injuries. Our data show that further, prospective investigation into the longboarding population demographics and injury patterns is necessary to contribute to effective injury prevention in this population.